The Lifestyle-integrated Functional Exercise (LiFE) program and its modifications: a narrative review - Hezel, Natalie; Körbi, Carlotta; Wolf, Melissa Madeleine; Adams, Michael; Jansen, Carl-Philipp; Labudek, Sarah; Wolf-Belala, Nacera; Kramer-Gmeiner, Franziska; Nerz, Corinna; Schwenk, Michael (German journal of exercise and sport research, 2021)
Lifestyle-integrated exercise is a promising approach to increase adherence levels of older adults compared to structured exercise programs as it saves time and effort and supports older adults in preventing falls and functional decline. The Lifestyle-integrated Functional Exercise (LiFE) program embodies this approach by integrating physical activity, balance, and strength activities into daily tasks of community-dwelling older adults aged 70+. A randomized controlled trial shows strong effectiveness of the original, resource-intensive one-on-one format of the LiFE program in terms of reducing falls, improving motor performance, and increasing physical activity. The positive effects of the original LiFE program have yet stimulated adaptions to group-based and information and communications technology-based formats, to younger seniors, for multicomponent interventions, and to populations with disabilities which resulted in 16 known studies about LiFE modifications. Evidence for the effectiveness of specific LiFE modifications exists for four programs, while seven adaptions are in the feasibility stage and one is still in the early development phase. A decade of existing LiFE research is summarized in this narrative review that, to the best of our knowledge, does not exist until now. The aim of this article is (1) to provide an overview of the number of LiFE modifications and their specifications, (2) to describe the current evidence regarding feasibility and effectiveness, and (3) to present challenges and potential of the different LiFE modifications. All adaptions of the LiFE program embody the benefits of the lifestyle-integrated approach and enable an enhancement of the successful LiFE concept.
Gesehen am 30.08.2023